Self-esteem, social identity and intergroup bias in two ethnic groups - Jelić, Margareta (2004)
Social Identity Theory (SIT) is based on the assumption that individuals strive to maintain or enhance positive identity because it supplies them with feeling of security, positive self-esteem and self-worth. Positive self-concept can be based on individual characteristics (personal identity) and characteristics of the groups one belongs to (social identity). In order to develop positive social identity connected to a membership in a certain group, it is important to evaluate the group positively and favourably in comparison to other groups. In doing this, people often evaluate in-group members more positively than outgroup members and sometimes even derogate outgroup members. TSI has given self-esteem a central role in explaining in-group bias and outgroup derogation. However, both the theoretical and empirical bases of the self-esteem hypothesis are largely rooted in research using the minimal group paradigm. The aim of this research was to test basic assumptions of Social Identity Theory on two ethnic groups living in a community divided along ethnic lines. We tested the hypothesis that personal and social self-esteem are predictors of in-group bias and out-group derogation and that social membership in majority or minority group may underlie discriminatory behavior. This research highlighted the importance of social identity and social self-esteem in intergroup processes, and also indicated a possible role of personal self-esteem. Nevertheless, self-esteem appears to provide only a partial explanation, and a variety of more or less powerful alternative social motives may underlie discriminatory behavior. The importance of belonging to a majority or minority ethnic group has also been considered.
Projekt MZOS
ENG